Transcriptional Repressor HIC1 Contributes to Suppressive Function of Human Induced Regulatory T Cells - Ubaid Ullah; Syed Bilal Ahmad Andrabi; Subhash Kumar Tripathi; Obaiah Dirasantha; Kartiek Kanduri; Sini Rautio; Catharina C. Gross; Sari Lehtimäki; Kanchan Bala; Johanna Tuomisto; Urvashi Bhatia; Deepankar Chakroborty; et al. (CELL PRESS, 2022)
Regulatory T (Treg) cells are critical in regulating the immune response. In vitro induced Treg (iTreg) cells have significant potential in clinical medicine. However, applying iTreg cells as therapeutics is complicated by the poor stability of human iTreg cells and their variable suppressive activity. Therefore, it is important to understand the molecular mechanisms of human iTreg cell specification. We identified hypermethylated in cancer 1 (HIC1) as a transcription factor upregulated early during the differentiation of human iTreg cells. Although FOXP3 expression was unaffected, HIC1 deficiency led to a considerable loss of suppression by iTreg cells with a concomitant increase in the expression of effector T cell associated genes. SNPs linked to several immune-mediated disorders were enriched around HIC1 binding sites, and in vitro binding assays indicated that these SNPs may alter the binding of HIC1. Our results suggest that HIC1 is an important contributor to iTreg cell development and function.